KONTRIBUSI USAHA TANAMAN HIAS DI PEKARANGAN TERHADAP PENDAPATAN KELUARGA DI KELURAHAN KAKASKASEN DUA KECAMATAN TOMOHON UTARA KOTA TOMOHON (The Contribution Of Ornamental Plant Businesses In Yard To Family Income In Kakaskasen Dua Village, Tomohon Utara Sub District, Tomohon City) - Emia Vlora Br Sembiring; Paulus A. Pangemanan; Yolanda P. I. Rori (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2021)
The objective of this research is to determine how much the contribution of the ornamental plant business in the yard to family income in Kakaskasen Dua Village, North Tomohon Sub District. The data used in this study are primary data and secondary data, The primary data used the census method with 8 respondents. Secondary data were obtained through direct interviews with 8 respondents and related parties to the study using a questionnaire and secondary data were obtained from the internet, the Central Bureau of Statistics of Tomohon City, and various literatures related to this study. The research results showed that the contribution that the ornamental plant business in the yard contributed to family income was 48.3%. The amount of income obtained from the ornamental plant business in the yard has an average of Rp. 3,584,852 and the average income outside the ornamental plant business is Rp. 3,831,250 with a contribution of 51.7%. This shows that the ornamental plant business in the yard has a large contribution to family income.Keywords: Contribution, Income, Ornamental Plant Business, Yard